2018
DOI: 10.1002/jbm.a.36435
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and clinical potential on decellularized adipose tissue

Abstract: Natural and synthetic materials have been developed to provide a three-dimensional (3-D) scaffold that mimics the extracellular matrix properties for tissue regeneration and reconstruction. On account of the excellent biological and mechanical properties, diverse decellularized tissue materials have been developed as natural scaffolds. Among them, decellularized adipose tissue (DAT) has generated great interest in recent years due to the extensiveness of the source and the eximious potential to enhance the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
(367 reference statements)
0
15
0
Order By: Relevance
“…The results revealed that the retention of collagen I and laminin was significantly reduced in SDAT and VDAT compared to native tissue, but the collagen IV is well preserved in decellularized tissue (Figure 7(a)). The reduction in collagen I and laminin in decellularized tissue compared to native tissue may be ascribed to the damage caused by chemical agents during decellularized process, 20,62 emphasising the importance of an optimal decellularization strategy that could achieve a good balance between optimal decellularization and maintaining matrix physical properties. 63,64 Further analysis demonstrated a significant higher relative expression of collagen I in SDAT than in VDAT and a weak mechanical strength of VDAT compared with SDAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the retention of collagen I and laminin was significantly reduced in SDAT and VDAT compared to native tissue, but the collagen IV is well preserved in decellularized tissue (Figure 7(a)). The reduction in collagen I and laminin in decellularized tissue compared to native tissue may be ascribed to the damage caused by chemical agents during decellularized process, 20,62 emphasising the importance of an optimal decellularization strategy that could achieve a good balance between optimal decellularization and maintaining matrix physical properties. 63,64 Further analysis demonstrated a significant higher relative expression of collagen I in SDAT than in VDAT and a weak mechanical strength of VDAT compared with SDAT.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In recent years, several groups have been testing DAT in vitro and in vivo for potential clinically translatable, tissue-engineering applications. [18][19][20] Most recently, Kokai et al 21 reported a first allograft implantation of DAT in the dorsal wrist of patients. The DAT matrix maintained softtissue volume in the dorsal wrist in a 4-month investigation with no severe adverse events and adipogenesis was found in the matrix, indicating that DAT could serve as a biomaterial product for clinical soft-tissue filling in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for decellularizing adipose tissue was pioneered by Flynn and colleagues [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and has since been confirmed by multiple independent laboratories [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. These methods combine biological (enzyme digestion), chemical, and physical processing steps to achieve the uniform and consistent manufacture of protein scaffolds depleted of contaminating genomic DNA and lipids.…”
Section: Extracellular Matrix (Ecm) From Decellularized Adipose Timentioning
confidence: 99%
“…Decellularized tissue. The acellular tissue matrix is a product of the decellularization process including a chemical or physical method for removing antigens associated with rejection in tissue transplantation [ 19 , 20 ]. It is a new type of biomaterial and is mainly used for the repair of cosmetic injury tissues, especially skin transplantation after burns.…”
Section: Classification Of Plastic Cosmetic Materialsmentioning
confidence: 99%
“… Examples of main materials used in plastic and cosmetic surgery. ( A ) Images of native and decellularized adipose tissue [ 20 ]. ( B ) The pre-shaped PLA inner core sandwiched between the pair of pre-shaped PGA layers for ear reconstruction [ 58 ].…”
Section: Figurementioning
confidence: 99%